DARI AMONG KE MICROLEARNING: TELAAH FILOSOFIS PEMIKIRAN KI HADJAR DEWANTARA DALAM PEMBELAJARAN MATEMATIKA DIGITAL - Dyah Ayu Sulistyaning Cipta; Dedi Kuswandi; Agus Wedi (Universitas Insan Budi Utomo, 2026)
The rapid development of digital technology has led to the emergence of various innovative learning approaches, one of which is microlearning, characterized by short, focused, and flexible learning units. However, studies on microlearning are often dominated by technical and instrumental perspectives, with limited attention to philosophical foundations of education, including in the context of mathematics education. This article aims to analyze the relevance of Ki Hadjar Dewantara’s educational philosophy, particularly the Among System, to the implementation of microlearning in digital learning, with a focus on mathematics learning. This study employed a qualitative approach using a library research design. Data were obtained from Ki Hadjar Dewantara’s original works as primary sources and from scholarly articles and books on microlearning and mathematics education as secondary sources. Data analysis was conducted through content analysis, philosophical interpretation, and conceptual comparison. The findings indicate that the principles of the Among System, which emphasize guidance based on learners’ nature and the demands of the times, are conceptually aligned with the characteristics of microlearning, which is learner-centered, flexible, and contextual. In mathematics education, microlearning has the potential to support gradual conceptual understanding through structured, small learning units. These findings suggest that microlearning can be understood as a pedagogical strategy that is philosophically and educationally grounded when implemented beyond purely technological considerations.